Philosophical-methodological aspects of knowledge in the game medium (Texas Journal of Philology, Culture and History, 2023)
This article provides enough information about the history of the game's development, content, goals and objectives. It has been revealed that the development of game technologies is a pedagogical problem in the eyes of scientists.